ANALISIS DESKRIPTIF FATHERLESS PADA PRIA DEWASA DENGAN ORIENTASI GAY - Natiyan Fajar Nugroho; Monty P Satiadarma; Untung Subroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The phenomenon of fatherlessness is an important issue in children's psychosocial development, especially for boys who need a father figure as a model for gender identification. A number of theories and studies show that the absence of a father can affect emotional and relational development, as well as the formation of self-identity into adulthood. This study aims to obtain an overview of the level of fatherlessness among gay men in the DKI Jakarta area. The method used is descriptive quantitative with purposive sampling technique. There were 248 gay men aged 19-40 years who filled out the Indonesian version of the Father Presence Questionnaire (FPQ). Descriptive analysis results showed that the level of fatherlessness was in the high category with an average score of 145.25 and a standard deviation of 25.68. A total of 201 respondents (81.05%) were classified as having high fatherlessness, while 47 respondents (18.95%) were classified as having low fatherlessness. The Relationship with the Father dimension received the highest score, indicating a lack of emotional closeness, involvement, and physical presence of the father as the most dominant form of fatherlessness. Overall, the findings illustrate that most participants experienced low father involvement during their growth and development.